Antibacterial effect of non-thermal atmospheric plasma against soft rot bacteria on paprika. (January 2020) - Go, Seon-Min; Kim, Hyun-Seung; Park, Mi-Ri; Jeong, Rae-Dong
Abstract: Non-thermal atmospheric plasma (NTAP) was examined for its antibacterial activity of Pectobacterium carotovorum subsp. carotovorum on paprika. Bacterial populations were completely inhibited in response to NTAP treatment at 1000 W for 30 s–90 s. To further assess the mechanisms that NTAP treatment inactivates bacterial populations, the morphology and membrane damage of bacterial cells were analyzed. The bacterial cells treated with NTAP for 90 s at 1000 W exhibited noticeable disruption, hollowness, and roughness on the outer membrane surfaces accompanied by severe loss in membrane integrity, which indicates that cell death was caused by this significant membrane damage. NTAP treatment for 90 s induced DNA leakage from the Pcc membrane and caused significant DNA damage as assessed by qRT-PCR. On in vivo test, NTAP-treated paprika showed antibacterial effects by 40% compared to untreated samples. Our findings suggest the high applicability of NTAP in controlling postharvest bacteria and ensuring the preservation of paprika. Highlights: Non-thermal atmospheric plasma (NTAP) inhibits the growth of Pectobacterium carotovorum subsp. carotovorum ( Pcc) in vitro and in vivo. Pcc inhibition is significantly dependent on treatment time. The antibacterial activity of NTAP is associated with membrane and DNA integrity.